Evaluation of the hepatoprotective effect of Yigan mingmu oral liquid against acute alcohol-induced liver injury in rats - Qigui Mo; Gao Zhou; Baibo Xie; Bingxin Ma; Xinyu Zang; Yuxin Chen; Linyou Cheng; James Hua Zhou; Youwei Wang (BMC, 2020)
Abstract Background Yigan mingmu oral liquid (YGMM) is a herbal medicine based on a famous Chinese herbal formula that has been used for sore eyes for more than 400 years. Eye health is closely associated with the liver based on TCM. This study aimed to investigate the hepatoprotective effect of YGMM against acute liver injury induced by alcohol in rats. Methods Experimental rats were administered with silymarin and YGMM through the gastric gavage during the entire experiment. Starting from the 11th day, the rats were administered orally with 14 ml/kg Red Star Erguotou Liquor, a popular brand, at 4 h after the dose of silymarin (100 mg/kg) and YGMM (1, 2.5 and 5 ml/kg in low, middle and high dosage group, respectively) once a day for 4 weeks except for the rats in the normal group. Biochemical parameters, including ALT, AST, TB, TG, T-SOD, GSH, and MDA were detected to evaluate the protective effect of YGMM. Pathological changes were observed through histopathological examination. Results Treatment with YGMM exhibited a significant protective effect by reversing the biochemical parameters (ALT, AST, TB, TG, and GSH) and histopathological changes. Histopathological examination by Oil Red O Staining Solution showed that lipid droplets were significantly reduced in the silymarin and YGMM groups (p < 0.001) when compared to alcohol group. Conclusions YGMM exhibits a significant hepatoprotective activity against acute liver injury induced by alcohol in rats.